2008
DOI: 10.1158/0008-5472.can-08-1259
|View full text |Cite
|
Sign up to set email alerts
|

Ugene, a Newly Identified Protein That Is Commonly Overexpressed in Cancer and Binds Uracil DNA Glycosylase

Abstract: Expression microarrays identified a novel transcript, designated as Ugene, whose expression is absent in normal colon and colon adenomas, but that is commonly induced in malignant colon cancers. These findings were validated by real-time PCR

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 16 publications
0
35
1
Order By: Relevance
“…While our current emphasis is focused on FAM72A (Ugene), it is uncertain, at present, as to whether additional members of the FAM72 family are functionally divergent or show similar function to LMPIP (Ugene, FAM72A), which awaits further studies. Also, the results from our current studies of LMP1-induced Ugene in the context of EBV infection and NPC are at variance with those found in the original discovery of Ugene (Guo et al, 2008). The reasons for this difference are currently unknown, but it is tempting to speculate that the different results may be the result of our emphasis on the initial steps in the induction of Ugene expression and function as a consequence of EBV infection or LMP1 overexpression, rather than being on the 'stationary' phase in the existing tumor cells.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…While our current emphasis is focused on FAM72A (Ugene), it is uncertain, at present, as to whether additional members of the FAM72 family are functionally divergent or show similar function to LMPIP (Ugene, FAM72A), which awaits further studies. Also, the results from our current studies of LMP1-induced Ugene in the context of EBV infection and NPC are at variance with those found in the original discovery of Ugene (Guo et al, 2008). The reasons for this difference are currently unknown, but it is tempting to speculate that the different results may be the result of our emphasis on the initial steps in the induction of Ugene expression and function as a consequence of EBV infection or LMP1 overexpression, rather than being on the 'stationary' phase in the existing tumor cells.…”
Section: Discussioncontrasting
confidence: 94%
“…Interestingly, Guo et al (2008) showed that Ugene-encoded protein is localized in the nucleus and interacts with uracil DNA glycosylase 2, a base excision repair enzyme involved in DNA repair pathways, the alteration of which has often been noted in cancers. These results suggested the potential involvement of Ugene in tumorigenesis; however, as the investigators noted, when tested in epithelial or fibroblasts, no oncogenic activity of Ugene could be demonstrated and no apparent influence on the regulation of uracil DNA glycosylase 2 repair activity was found in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead discovery by protein-ligand-binding-site prediction Since FAM72A plays a significant role in tumorigenesis [3,4], the present study on the theoretical 3D protein structure modeling of FAM72A led us to search for a potential ligandbinding site of FAM72A as the identification of proteinligand-binding sites is a decisive pathway for the elucidation of protein function and development of therapeutics. A metaserver approach (e.g., via http://zhanglab.ccmb.med.umich.…”
Section: Protein Structure Evaluationmentioning
confidence: 99%
“…Using these methods, we discovered the new membrane-bound FAM72A protein (also known as p17, Ugene, or LMPIP) with demonstrated highly promising clinical relevance to survival/ death outcomes in patients with various kinds of cancers, as it can be linked to tumorigenic effects in non-neuronal tissues [2][3][4]. Our group also unraveled FAM72A's mode of action, and our data demonstrate that FAM72A interacts with various tumor suppressor proteins that are (epi-) genetically modified in cancer [3] and thus, interference with FAM72A's activities might be a novel option to influence the tumor suppressor protein p53 signaling pathways for the treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%